THE ESSENCE OF AUDIT OPINION AND ITS IMPORTANCE FOR USERS OF FINANCIAL STATEMENTS - Aybek Nazarboevich Abdullaev; Yaqubova Feruza Mavlonberdiyevna (PEDAGOGS, 2024)
Abstract. The article attempts a scientific analysis of the subjective and virtually unregulated by law, but at the same time the most significant category in the economic and legal field is "auditor's opinion". The limited availability of such information in the theory of auditing is a serious problem, since the practice of choosing one or another form of audit opinion still reveals unresolved issues and contradictions regarding the correctness of the auditor's expressed opinion. The purpose of the article is to study the content of the concept of "auditor's opinion" in the historical and theoretical aspect and identify problematic areas of its formation in the conditions of imperfection of current legislation in order to increase the objectivity of assessing the reliability of financial statements. The research is based on the use of general scientific methods of comparison, analysis, generalization using critical assessment, historical and logical approaches implemented using the dialectical method of cognition. Based on the studied works of Russian and foreign scientists, the paper presents the author's vision of the emergence and development of the concept of “auditor's opinion”.